Outcome analysis of stage I epithelial‐predominant favorable‐histology Wilms tumors: A report from Children's Oncology Group study AREN03B2. Issue 12 (8th April 2020) - Parsons, Lauren N.; Mullen, Elizabeth A.; Geller, James I.; Chi, Yueh‐Yun; Khanna, Geetika; Glick, Richard D.; Aldrink, Jennifer H.; Vallance, Kelly L.; Kim, Yeonil; Fernandez, Conrad V.; Dome, Jeffrey S.; Perlman, Elizabeth J.
Abstract : Background: Stage I epithelial‐predominant favorable‐histology Wilms tumors (EFHWTs) have long been suspected to have an excellent outcome. This study investigates the clinical and pathologic features of patients with stage I EFHWTs to better evaluate the potential for a reduction of chemotherapy and its associated toxicity. Methods: All patients registered in the Children's Oncology Group (COG) AREN03B2 study between 2006 and 2017 with stage I EFHWTs were identified. EFHWTs were defined as tumors with at least 66% epithelial differentiation, regardless of the degree of differentiation. Clinical information was abstracted from COG records. Event‐free survival (EFS) and overall survival (OS) were calculated and compared between groups based on age and therapy. Results: The 4‐year EFS rate was 96.2% (95% confidence interval, 92%‐100%), and the OS rate was 100%; EFS and OS did not statistically significantly differ with the age at diagnosis (<48 vs ≥48 months; P  = .37) or treatment (EE4A vs observation only; P  = .55). Six events were reported. Three patients developed contralateral tumors and did not otherwise relapse; none of these had nephrogenic rests or a recognized predisposition syndrome. Three patients developed metastatic recurrence; all 3 had received EE4A as their primary therapy after nephrectomy. Conclusions: These findings demonstrate an excellent outcome for stage I EFHWTs with >95% EFS and OS. These data support the utility of investigating the treatment of stage I EFHWTs with observation alone after nephrectomy. Abstract : Children with stage I epithelial‐predominant favorable‐histology Wilms tumors have excellent event‐free and overall survival, regardless of age or treatment regimen. These data support the potential utility of investigating the treatment of stage I epithelial‐predominant favorable‐histology Wilms tumors with observation alone after nephrectomy.